The subjectivity made norm: stories and systems in the newsgames or informative video games - Peribáñez Faguas, Santiago (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The journalistic storytelling is constructed on a fine line between the desired objectivity and the subjectivity of every subject. The degrees of relationship between both of them have established journalistic genres that have helped producers and consumers identify each text and its message. Such taxonomy is not completely operative in a new environment where formats such as newsgames arise; the different levels of the videoludic story show in very different ways the subjectivities of the creative process. The present article breaks down the resources of newsgames that can be impregnated with this subjectivity and how it is shown to the final reader. To support this explanation, the second part of the text includes the analysis of one of the most complex newsgames developed in Spain: Montelab, work of the Lab RTVE.
Keywords: newsgames; video games; journalism; subjetivity; game design